Pengaruh Kompensasi dan Gaya Kepemimpinan terhadap Loyalitas Karyawan melalui Kepuasan Kerja sebagai Variabel Intervening (Studi Kasus pada PT. Fortech Indotama Jakarta) - Sitorus, Ramli Parulian; Prasilowati, Sri Lestari (Jurnal EMT KITA, 2026)
The objectives of this study are as follows: 1) To determine and analyze the effect of compensation on employee loyalty at PT. Fortech Indotama Jakarta. 2) To determine and analyze the effect of leadership style on employee loyalty at PT. Fortech Indotama Jakarta. 3) To determine and analyze the effect of compensation on job satisfaction of employees at PT. Fortech Indotama Jakarta. 4) To determine and analyze the effect of leadership style on job satisfaction of employees at PT. Fortech Indotama Jakarta. 5) To determine and analyze the effect of job satisfaction on employee loyalty at PT. Fortech Indotama Jakarta. 6) To determine and analyze the effect of compensation on employee loyalty through job satisfaction as an intervening variable at PT. Fortech Indotama Jakarta. 7) To determine and analyze the effect of leadership style on employee loyalty through job satisfaction as an intervening variable at PT. Fortech Indotama Jakarta. The results of this study indicate that: 1) Compensation has a significant effect on employee loyalty. 2) Leadership style has a significant effect on employee loyalty. 3) Compensation has a significant effect on job satisfaction. 4) Leadership style has a significant effect on job satisfaction. 5) Job satisfaction has a significant effect on employee loyalty. 6) Compensation has a significant effect on employee loyalty through job satisfaction. 7) Leadership style has a significant effect on employee loyalty through job satisfaction.